Odpowiedź odpowiedzialności - Kubicka, Dorota (Filozofia Publiczna i Edukacja Demokratyczna, 2017)
In philosophical thought of Janusz Korczak the idea of human freedom was connected with concepts of free will and responsibility. In this discussion man’s overexposed need for safety, was seen as biggest threat to freedom. Therefore Korczak argued with middle-class morality, which he was seeing as weak and lacking of spiritual core. Korczak had no doubts, that children should learn the basics of freedom by participating in decision concerning their own lives.